Perceptions of cardiac care providers towards oral health promotion in Australia. Issue 5 (October 2018) - Sanchez, Paula; Everett, Bronwyn; Salamonson, Yenna; Ajwani, Shilpi; Bhole, Sameer; Bishop, Joshua; Lintern, Karen; Nolan, Samantha; Rajaratnam, Rohan; Redfern, Julie; Sheehan, Maria; Skarligos, Fiona; et al.
Abstract: Background: There is increasing evidence linking poor oral health with cardiovascular disease and it is recommended that health professionals managing people with cardiac disease (cardiac care providers) promote oral health in their practice. However, the current perceptions of cardiac care providers regarding this aspect of clinical practice are unknown in Australia. Aim: To explore oral health perceptions, knowledge and practices of cardiac care providers and their role in promoting oral health. Methods: A qualitative study involving focus groups and semi-structured telephone interviews was undertaken with cardiac care providers (27 nurses, two physiotherapists, one exercise physiologist) across Australia between January–March 2016. Interviews/focus groups were transcribed and thematically analysed. Findings: Most participants encountered a number of patients with poor oral health and highlighted barriers seeking dental care, including access, cost and lack of awareness. However, oral health was not routinely discussed with patients except when cardiac valve surgeries were required. Many participants were unaware of the relationship between oral health and cardiovascular disease. Overall, participants were comfortable with promoting oral health if barriers such as training, time constraints and referral pathways were addressed. Practical suggestions regarding timing of training, preferred content and delivery format were also provided. Discussion: Cardiac care providers have limited oral health knowledge and are not routinely promoting oral health. However, they are receptive to promoting oral health with adequate support. Conclusion: Cardiac care providers need to be adequately trained and supported to promote oral health to their patients. Supportive strategies could include training, resources and formalised referral pathways.